Hubungan Pengetahuan Perawatan Rambut dengan Perilaku Merawat Rambut Berjilbab pada Mahasiswi Tata Rias Universitas Negeri Jakarta - Alya Juwita Zahira; Mari Okatini Armandari; Neneng Siti Silfi Ambarwati (Mathematics Education Study Program, 2025)
This study aims to identify and analyze the relationship between hair care knowledge and hair care behavior in cosmetology education students of Jakarta State University. The population of this study was cosmetology students of Jakarta State University class of 2020-2023 as many as 183 students with a sample technique taken, namely purposive sampling from the population to 97 samples of veiled students. The results show that students have knowledge of hair care knowledge with a mean value of 4.46 and a mean value of hair care behavior with a veil of 52.61. In the linearity test analysis results showed a significant linear relationship between knowledge and behavior (p = 0.050). In the partial test (t-test) the result obtained is a significance value of 0.000. Therefore, it can be concluded that 0.000 <0.050 which indicates that Ho is rejected and Ha is accepted, meaning that the independent variable (X) has a significant relationship with the dependent variable (Y). Through the coefficient of determination test, a value of 0.134 is obtained, which means that the relationship between variable X (hair care knowledge) and variable Y (hair care behavior on the headscarf of Jakarta State University Cosmetology students) only contributes 13.4%. While the remaining 86.6% is another factor not examined in this study. This study provides important implications regarding the need for more intensive hair care education for female students wearing hijab in order to support their hair health.